A solid electrolyte and its preparation method and application

By introducing solid electrolytes of cyclotriphosphazene derivative-nanoceramic composite materials into lithium sulfur batteries, the problems of polysulfide shuttle effect and lithium dendrites in lithium sulfur batteries are solved, and the cycle life and capacity retention rate of the battery are significantly improved.

CN118398887BActive Publication Date: 2025-04-11河源市联懋新材料有限公司
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410638552.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-22
Publication Date
2025-04-11
Estimated Expiration
2044-05-22

AI Technical Summary

Technical Problem

The shuttle effect of polysulfides in lithium-sulfur batteries and the side reaction of lithium metal negative electrodes leads to rapid attenuation of battery capacity and shortening service life, making it difficult for the prior art to achieve quantitative production.

Method used

The cyclotriphosphazene derivative-nanoceramic composite is used as the key component of the solid electrolyte, and the shuttle of polysulfides is blocked through chemical adsorption and the growth of lithium dendrites on the surface of the negative electrode is inhibited.

Benefits of technology

It effectively avoids the capacity attenuation of lithium-sulfur batteries, improves the cycle life of the battery, and maintains a good charging and discharging specific capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118398887B_ABST
    Figure CN118398887B_ABST
Patent Text Reader

Abstract

The present invention discloses a solid electrolyte, and the raw materials for preparation include by weight percentage: 40-75wt% of lithium source, 10-30wt% of cellulose, 5-20wt% of polymer, 5-15wt% of cyclotriphosphazene-nano-ceramic composite, and the raw materials for preparation also include 15-50mL of a first solvent. The present invention prepares a solid electrolyte for application in a lithium-sulfur battery by introducing a cyclotriphosphazene derivative-nano-ceramic composite material, and chemical adsorption effectively blocks the shuttle of sulfur positive electrodes, avoids corrosion of lithium negative electrodes and generation of lithium dendrites, reduces the attenuation rate of battery capacity, and improves the cycle life of lithium-sulfur batteries. The present invention controls the particle size of nano-ceramic silicon dioxide in the cyclotriphosphazene derivative-nano-ceramic composite material to be 50nm-1000nm, which can maintain a good charge and discharge specific capacity of the lithium-sulfur battery and avoid the battery efficiency of the lithium-sulfur battery from decreasing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid electrolyte and a preparation method and application thereof, and relates to H01M, and in particular to the field of devices for directly converting chemical energy into electrical energy. Background Art

[0002] Lithium-sulfur batteries have a high theoretical specific capacity and are therefore considered to be new energy batteries with great potential for application and development. However, in liquid electrolyte systems, the polysulfide shuttle effect in lithium-sulfur batteries, the side reactions of lithium metal negative electrodes, and lithium dendrites on the negative electrode surface will cause the battery capacity of lithium-sulfur batteries to decay rapidly, shortening the service life of lithium-sulfur batteries and seriously affecting the practical application of lithium-sulfur batteries. Existing methods to solve the sulfide shuttle effect of lithium-sulfur batteries include positive electrode sulfide modification, negative electrode isolation and other methods, but the process of electrode modification is complicated and cannot be mass-produced at this stage.

[0003] Chinese invention patent CN201710386734.1 discloses a gelable system containing inorganic nanoparticles, a preparation method and application thereof, and adopts cyclic ether compounds. By adjusting the content and type of lithium salts, cyclic ether compounds and inorganic nanoparticles in the system, a solid electrolyte with adjustable strength, adjustable time and adjustable transition temperature can be prepared. However, after being applied to lithium-sulfur batteries, the cycle specific capacity is not significantly improved and the effect is not good. Chinese invention patent CN201710019490.3 discloses a solid electrolyte material for lithium batteries, a preparation method and application thereof, and adopts a metal organic framework compound with a rich pore structure to provide a good channel for the transport of lithium ions, with high ionic conductivity, and can improve the stability of the battery. However, the improvement effect on the shuttling problem of polysulfides in lithium-sulfur batteries is not good, and it is not suitable for application in lithium-sulfur batteries. Summary of the invention

[0004] In order to avoid the shuttle effect of polysulfides in lithium-sulfur batteries and reduce negative electrode side reactions of lithium-sulfur batteries, the first aspect of the present invention provides a solid electrolyte, which includes: 40-75wt% of lithium source, 10-30wt% of cellulose, 5-20wt% of polymer, and 5-15wt% of cyclotriphosphazene-nano-ceramic composite.

[0005] As a preferred embodiment, the cellulose is selected from one or a combination of cellulose acetate, cellulose nitrate, hydroxypropyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, hydroxypropyl methyl cellulose and methyl cellulose.

[0006] As a preferred embodiment, the polymer is selected from one or a combination of polysiloxane, polyethylene glycol succinate, poly(ethylene glycol) methyl ether acrylate, poly-1,3-dioxolane, polycyanoacrylate, polycarbonate, polyacrylamide, polyethylene oxide.

[0007] As a preferred embodiment, the lithium source is selected from one or a combination of lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl imide), lithium hexafluorophosphate, lithium dioxalatoborate, lithium difluorophosphate, and lithium bis(fluorosulfonyl imide).

[0008] As a preferred embodiment, the raw materials for preparing the cyclotriphosphazene-nano-ceramic composite include 0.2-8 parts by weight of cyclotriphosphazene derivative, 2-15 parts by weight of nano-ceramic material, 0.05-3 parts by weight of silane coupling agent, and 23-80 parts by weight of second solvent.

[0009] As a preferred embodiment, the first solvent and the second solvent are the same or different, and the first solvent and the second solvent are selected from one or a combination of acetone, dimethylformamide, toluene, dichloromethane, chloroform, acetonitrile, phenol, and ether.

[0010] As a preferred embodiment, the cyclotriphosphazene derivative is selected from one or a combination of hexachlorocyclotriphosphazene, hydroxy(pentafluoro)cyclotriphosphazene, epoxy(pentafluoro)cyclotriphosphazene, amino(pentafluoro)cyclotriphosphazene, aryloxy(pentafluoro)cyclotriphosphazene and alkoxy(pentafluoro)cyclotriphosphazene.

[0011] As a preferred embodiment, the particle size of the nano-ceramic material is 50-1000 nm.

[0012] As a preferred embodiment, the nano-ceramic material is selected from one or a combination of metal oxide nano-ceramics, nitride nano-ceramics, carbide nano-ceramics, boride nano-ceramics, silicide nano-ceramics, fluoride nano-ceramics, and sulfide nano-ceramics.

[0013] As a preferred embodiment, the silicide nanoceramic is selected from one or a combination of silicon dioxide nanoceramics, silicate nanoceramics, silicon nitride, and silicon carbide.

[0014] The applicant discovered during the experiment that by introducing cyclotriphosphazene derivatives-nano-ceramic composite materials into lithium-sulfur batteries to prepare solid electrolytes, the dissolution and shuttling of polysulfides in the electrolyte can be avoided, while the growth of lithium dendrites on the negative electrode surface can be inhibited, effectively solving the problem of battery capacity decay. It is speculated that the possible reasons are: the cyclotriphosphazene derivatives-nano-ceramic composite materials have excellent adsorption effects, which can effectively block the "shuttling" of polysulfides on the sulfur positive electrode side through chemical adsorption, and the cyclotriphosphazene derivatives-nano-ceramic composite materials have a large modulus, which can inhibit the growth of lithium dendrites on the negative electrode surface and avoid corrosion of the lithium negative electrode, thereby reducing the capacity decay rate of lithium-sulfur batteries and improving the cycle life of lithium-sulfur batteries.

[0015] The applicant further discovered that it is necessary to control the particle size of nano-ceramic silica in the cyclotriphosphazene derivative-nanoceramic composite material to 50nm-1000nm. If the particle size of silica is too large, it will affect the transmission of sulfur ions in the electrolyte and reduce the battery efficiency of the lithium-sulfur battery. If the particle size of silica is too small, the adsorption effect of silica and cyclotriphosphazene derivatives will decrease, and the best technical effect of solving the "shuttle" problem cannot be achieved.

[0016] As a preferred embodiment, the silane coupling agent is selected from one or a combination of vinyl silane, amino silane, epoxy silane, mercapto silane, and methacryloxy silane.

[0017] As a preferred embodiment, the preparation method of the cyclotriphosphazene-nano ceramic composite comprises the following steps:

[0018] H1: adding cyclotriphosphazene derivative, nano-ceramic material and silane coupling agent into the second solvent, heating and stirring, centrifuging at high speed after the reaction is complete, and removing the supernatant;

[0019] The lower layer was centrifuged and washed with H2 for several times to obtain a cyclotriphosphazene-nano-ceramic composite.

[0020] As a preferred embodiment, the stirring speed of the heating and stirring in step H1 is 200-1000 rpm, the stirring time is 30-300 min, the heating temperature is 60-120° C., the centrifugal speed is 5000-10000 rpm, and the centrifugal time is 30-180 s.

[0021] As a preferred embodiment, in step H2, a mixed solution of water and ethanol is used for washing, and the volume ratio of water to ethanol is 1:1.

[0022] As a preferred embodiment, the washing times in step H2 are 5-10 times.

[0023] A second aspect of the present invention provides a method for preparing a solid electrolyte, wherein the raw materials for preparing the solid electrolyte further include a first solvent, and the preparation steps are as follows:

[0024] S1 preparation of cyclotriphosphazene-nano ceramic composite;

[0025] S2: adding a lithium source, cellulose, a polymer, and the cyclotriphosphazene-nano-ceramic composite prepared in step S1 into a first solvent, heating and stirring, to prepare a solid electrolyte slurry;

[0026] S3: Smear the solid electrolyte slurry on a glass plate and obtain a solid electrolyte after vacuum drying.

[0027] As a preferred embodiment, in step S2, the heating temperature is 25-80° C., the stirring rate is 200-1000 rpm, and the stirring time is 6-24 h.

[0028] As a preferred embodiment, in step S3, the coating thickness is 30-200 μm, the vacuum drying temperature is 40-100° C., and the vacuum drying time is 3-24 h.

[0029] A second aspect of the present invention provides a lithium-sulfur battery comprising the solid electrolyte according to any one of claims 1 to 8.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) The solid electrolyte of the present invention is prepared by introducing a cyclotriphosphazene derivative-nano-ceramic composite material, which can avoid the dissolution and shuttling of polysulfides in the electrolyte and inhibit the growth of lithium dendrites on the negative electrode surface, effectively solving the capacity decay problem of the battery.

[0032] (2) The solid electrolyte of the present invention controls the particle size of nano-ceramic silicon dioxide in the cyclotriphosphazene derivative-nano-ceramic composite material to be 50nm-1000nm, so that the lithium-sulfur battery can maintain a good charge and discharge specific capacity and avoid the decrease of the battery efficiency of the lithium-sulfur battery.

[0033] (3) The solid electrolyte of the present invention is applied to lithium-sulfur batteries, which can effectively block the shuttling of sulfur positive electrodes by chemical adsorption, avoid the corrosion of lithium negative electrodes and the formation of lithium dendrites, reduce the attenuation rate of battery capacity, and improve the cycle life of lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Test picture of capacity retention rate of lithium-sulfur battery prepared by using solid electrolyte prepared in Example 1.

[0035] Figure 2Test picture of capacity retention rate of lithium-sulfur battery prepared with solid electrolyte prepared in Comparative Example 1. DETAILED DESCRIPTION

[0036] Example 1

[0037] A solid electrolyte, wherein the raw materials for preparation include: 23.45 g of a lithium source, 5.95 g of cellulose, 3.15 g of a polymer, 2.45 g of a cyclotriphosphazene-nano-ceramic composite, and 35 mL of a first solvent.

[0038] The lithium source is lithium bis(trifluoromethanesulfonyl)imide, the cellulose is cellulose acetate, the polymer is polyethylene oxide purchased from Acros with a brand number of 192230010, and the first solvent is acetonitrile.

[0039] The raw materials for preparing the cyclotriphosphazene-nano-ceramic composite include 3 g of cyclotriphosphazene derivative, 12 g of nano-ceramic material, 1.7 g of silane coupling agent, and 50 mL of a second solvent.

[0040] The cyclotriphosphazene derivative is hydroxy(pentafluoro)cyclotriphosphazene, the silane coupling agent is mercaptopropyltriethoxysilane, and the second solvent is acetonitrile.

[0041] The nano ceramic material is silicon dioxide, and the particle size is 200nm.

[0042] The preparation method of the cyclotriphosphazene-nano ceramic composite comprises the following steps:

[0043] H1: adding cyclotriphosphazene derivative, nano-ceramic material and silane coupling agent into the second solvent, heating and stirring, centrifuging at high speed after the reaction is complete, and removing the supernatant;

[0044] The lower layer was centrifuged and washed with H2 for several times to obtain a cyclotriphosphazene-nano-ceramic composite.

[0045] The stirring speed of the heating and stirring in step H1 is 800 rpm, the stirring time is 120 min, the heating temperature is 80° C., the centrifugal speed is 8000 rpm, and the centrifugal time is 120 s.

[0046] In the step H2, a mixed solution of water and ethanol is used for washing, and the volume ratio of water to ethanol is 1:1.

[0047] The washing times in step H2 are 5 times.

[0048] A method for preparing a solid electrolyte comprises the following steps:

[0049] S1 preparation of cyclotriphosphazene-nano ceramic composite;

[0050] S2: adding a lithium source, cellulose, a polymer, and the cyclotriphosphazene-nano-ceramic composite prepared in step S1 into a first solvent, heating and stirring, to prepare a solid electrolyte slurry;

[0051] S3: Smear the solid electrolyte slurry on a glass plate and obtain a solid electrolyte after vacuum drying.

[0052] In step S2, the heating temperature is 60° C., the stirring rate is 800 rpm, and the stirring time is 8 hours.

[0053] In the step S3, the coating thickness is 50 μm, the vacuum drying temperature is 70° C., and the vacuum drying time is 12 h.

[0054] Example 2

[0055] A solid electrolyte and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that the amount of lithium bistrifluoromethanesulfonyl imide added is 7.7 g.

[0056] Example 3

[0057] A solid electrolyte and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that the amount of lithium bistrifluoromethanesulfonyl imide added is 34.65 g.

[0058] Example 4

[0059] A solid electrolyte and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that the added amount of cellulose acetate is 5.13 g.

[0060] Example 5

[0061] A solid electrolyte and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that the added amount of cellulose acetate is 9.68 g.

[0062] Example 6

[0063] A solid electrolyte and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that the amount of polyethylene oxide added is 1.68 g.

[0064] Example 7

[0065] A solid electrolyte and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that the added amount of the polyethylene oxide is 7.96 g.

[0066] Example 8

[0067] A solid electrolyte and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that the added amount of the cyclotriphosphazene-nano-ceramic composite is 1.71 g.

[0068] Example 9

[0069] A solid electrolyte and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that the added amount of the cyclotriphosphazene-nano-ceramic composite is 5.74 g.

[0070] Example 10

[0071] A solid electrolyte and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that the nano-ceramic material is silicon dioxide with a particle size of 800 nm.

[0072] Embodiment 11

[0073] A solid electrolyte and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that the coating thickness in step S3 is 180 μm.

[0074] Example 12

[0075] A solid electrolyte and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that the lithium source is lithium bis(fluorosulfonyl)imide.

[0076] Embodiment 13

[0077] A solid electrolyte and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that the cellulose is nitrocellulose.

[0078] Embodiment 14

[0079] A solid electrolyte and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that the polymer is polyethylene glycol succinate, purchased from Aladdin with the brand name P111885.

[0080] Embodiment 15

[0081] A solid electrolyte and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that the cyclotriphosphazene derivative is amino(pentafluoro)cyclotriphosphazene.

[0082] Example 16

[0083] A solid electrolyte and a preparation method thereof, the specific implementation manner is the same as that of Example 1, except that the nano-ceramic material is aluminum oxide.

[0084] Comparative Example 1

[0085] A solid electrolyte, wherein the preparation raw materials include: 23.45 g of a lithium source, 5.95 g of cellulose, 3.15 g of a polymer, and 35 mL of a first solvent.

[0086] The lithium source is lithium bis(trifluoromethanesulfonyl)imide, the cellulose is cellulose acetate, the polymer is polyethylene oxide purchased from Acros with a brand number of 192230010, and the first solvent is acetonitrile.

[0087] A method for preparing a solid electrolyte comprises the following steps:

[0088] S1: adding a lithium source, cellulose, and a polymer into a first solvent, heating and stirring, to prepare a solid electrolyte slurry;

[0089] S2: Smear the solid electrolyte slurry on a glass plate and obtain a solid electrolyte after vacuum drying.

[0090] In step S2, the heating temperature is 60° C., the stirring rate is 800 rpm, and the stirring time is 8 hours.

[0091] In the step S3, the coating thickness is 50 μm, the vacuum drying temperature is 70° C., and the vacuum drying time is 12 h.

[0092] Performance Testing

[0093] The solid electrolyte prepared in the embodiment and the comparative example is matched with a sulfur positive electrode and a lithium metal negative electrode to assemble a lithium-sulfur battery, and the steps are as follows:

[0094] (1) Preparation of sulfur positive electrode: CNTs and elemental sulfur were mixed and ground in a mass ratio of 3:7, and the mixed powder was transferred to a 50 mL polytetrafluoroethylene reactor and heated at 155 °C for 12 h to obtain the positive electrode active material. The positive electrode active material, acetylene black, and polyvinylidene fluoride were mixed in a mass ratio of 7:2:1, and N-methyl-2-pyrrolidone was added. The slurry was prepared by grinding for 30 min and coated on the aluminum current collector. The slurry was dried at 80 °C for 12 h and sliced ​​to obtain a slurry with a loading of 2.5 mg cm -1 , a sulfur cathode sheet with a diameter of 12 mm;

[0095] (2) Assembly of button-type lithium-sulfur batteries: In an argon atmosphere glove box (oxygen content <0.01ppm, water content <0.01ppm), the positive electrode shell, sulfur positive electrode sheet, solid electrolyte, ionic liquid, lithium metal negative electrode, stainless steel gasket and stainless steel spring, and negative electrode shell are assembled into button-type batteries in order, and the batteries are sealed using a sealing machine.

[0096] The lithium-sulfur battery containing the solid electrolyte prepared in the above embodiment and comparative example was left to stand for 24 hours, and then subjected to charge and discharge test at 60°C. The results are shown in Table 1. Figure 1-2 .

[0097] Table 1

[0098]

[0099]

[0100] According to the comparison between Example 1 and Comparative Example 1 in Table 1, it can be seen that the new solid electrolyte provided by the present invention can significantly improve the capacity retention rate and average coulombic efficiency of lithium-sulfur batteries. According to Examples 1-9, it can be found that solid electrolytes composed of different contents of polymers, lithium salts, cellulose, and cyclotriphosphazene derivatives-nano-ceramic composite materials can improve the cycle performance of lithium-sulfur batteries to varying degrees. According to Examples 10-11, it was found that silicon dioxide of different particle sizes and different solid electrolyte thicknesses can improve the cycle performance of lithium-sulfur batteries, but the degree of improvement is different. According to Examples 12-16, it was found that adjusting the type of cyclotriphosphazene derivatives-nano-ceramic composite materials, polymers, cellulose or lithium salts has different degrees of improvement effects on the capacity retention rate and average coulombic efficiency of lithium-sulfur batteries.

Claims

1. A solid electrolyte, characterized in that Solid electrolytes include: 40-75wt% lithium source, 10-30wt% cellulose, 5-20wt% polymer, 5-15wt% cyclotriphosphazene-nano ceramic composite; The raw materials for preparing the cyclotriphosphazene-nano-ceramic composite include 0.2-8 parts by weight of a cyclotriphosphazene derivative, 2-15 parts by weight of a nano-ceramic material, 0.05-3 parts by weight of a silane coupling agent, and 23-80 parts by weight of a second solvent; The particle size of the nano ceramic material is 50-1000nm.

2. The solid electrolyte according to claim 1, characterized in that: The cellulose is selected from one or a combination of cellulose acetate, cellulose nitrate, hydroxypropyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, hydroxypropyl methyl cellulose and methyl cellulose.

3. The solid electrolyte according to claim 1, characterized in that: The polymer is selected from one or a combination of polysiloxane, polyethylene glycol succinate, poly(ethylene glycol) methyl ether acrylate, poly-1,3-dioxolane, polycyanoacrylate, polycarbonate, polyacrylamide, polyethylene oxide.

4. The solid electrolyte according to claim 1, characterized in that: The nano-ceramic material is selected from one or a combination of metal oxide nano-ceramics, nitride nano-ceramics, carbide nano-ceramics, boride nano-ceramics, silicide nano-ceramics, fluoride nano-ceramics and sulfide nano-ceramics.

5. The solid electrolyte according to claim 4, characterized in that: The silicide nano-ceramic is selected from one or a combination of silicon dioxide nano-ceramic, silicate nano-ceramic, silicon nitride and silicon carbide.

6. The solid electrolyte according to claim 1, characterized in that: The silane coupling agent is selected from one or a combination of vinyl silane, amino silane, epoxy silane, mercapto silane and methacryloxy silane.

7. A method for preparing a solid electrolyte according to any one of claims 1 to 6, characterized in that: The raw materials for preparing the solid electrolyte also include a first solvent, and the preparation steps are as follows: S1 preparation of cyclotriphosphazene-nano ceramic composite; S2: adding a lithium source, cellulose, a polymer, and the cyclotriphosphazene-nano-ceramic composite prepared in step S1 into a first solvent, heating and stirring, to prepare a solid electrolyte slurry; S3: Smear the solid electrolyte slurry on a glass plate and obtain a solid electrolyte after vacuum drying.

8. A lithium-sulfur battery, characterized in that: Comprising the solid electrolyte according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Solid electrolyte material for lithium battery and preparation method and application of solid electrolyte material

    CN106532112A

  • Gellable system containing inorganic nanometer particles, and preparation method and application thereof

    CN108963330A

  • Cellulose / polycarbonate solid polymer electrolyte and preparation method

    CN108832176A

  • Composite electrolyte for lithium-sulfur battery as well as preparation method and application thereof

    CN110931851A

  • Lithium-sulfur battery and preparation method thereof

    CN116895838A